COUNSELING AND MENTORING OF KAIZEN MANAGEMENT IMPLEMENTATION AT SRIJAYA CAR REPAIR SHOP SURABAYA - Yahya Yahya; Anton Eko Yulianto (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The purpose of community service activities (PKM) which is carried out through the activity of "Counseling and Mentoring in the Application of Kaizen Management at Srijaya car repair shop Surabaya" to improve the quality of services to consumers. Companies will be introduced to the concept of how to make continuous improvements, conducting improvements in small steps but consistently carried out on an ongoing basis. The implementation of Kaizen management with 5S principles (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) which means Concise, Neat, Clean, Caring, Diligent by utilizing the workplace which includes equipment, documents, buildings and space to train the habits of workers in an effort to improve discipline and work productivity. The Methods used are through four stages, namely: preparation, Kaizen management counseling, monitoring and evaluation. The results of this counseling and coaching activity show that there are still many step-by-step observations that must be addressed in this workshop to maximize the quality of services to consumers.